Simple Determination of Cystine in Artificial Urine and Drug Matrices Using Digital Image Colorimetry - Kustanto, Tulay Borahan; Zaman, Buse Tugba; Korkunc, Ummugulsum Polat; Gel, Mehmet Selim; Bakirdere, Sezgin (TAYLOR & FRANCIS INC, 2026)
Smartphone-based digital image colorimetry was developed for the determination of cystine in pharmaceutical formulations and artificial urine samples. A lab-made colorimetric box was designed for capturing the digital images of sample solutions using a smartphone. The developed method employs a simple colorimetric method called nitroprusside test which specifically targets free -SH groups. Cystine was reduced to cysteine before the colorimetric test was applied. The color intensity is inversely related to the concentration of the analyte. The best linearity was obtained with the G color channel. Digital image processing was performed using the RGB Color Detector mobile application to obtain analytical data. The developed method exhibited good linearity in the range of 29.7-00.3 mg/kg. The limits of detection and quantification were 9.7 mg/kg and 32.3 mg/kg, respectively. The percent recoveries were 104.2 +/- 7.8% and 108.7 +/- 4.6%, which proved the accuracy and applicability of the developed method.
Keywords: Cystine; determination; digital image colorimetry; smartphone; spectrophotometry; urine; AMINO-ACIDS; GOLD NANOPARTICLES; CYSTEINE; CHROMATOGRAPHY; VALIDATION; SAMPLES; FLUIDS; FILM; Chemistry